2011
DOI: 10.1186/1755-8166-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis and clinical manifestations of a case with de novo mosaic ring chromosome 7

Abstract: AimClinical and molecular cytogenetic investigations of a newborn girl exhibiting facial dysmorphism with developmental delay.MethodsPhenotypic evaluation was first applied to examine the proband's developmental status. Computed tomography and colour transcranial Doppler were used then to investigate her brain structure and function. Subsequently, chromosomal abnormalities were examined by karyotyping and fluorescent in situ hybridization was performed to investigate size of fragments lost at the two distal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Once the cells reached 50-60% confluence, they were washed twice with phosphate buffered saline (PBS), detached by 0.25% trypsin-EDTA (Gibco BRL) and then replated at a density of 3000 cells/cm 2 under the same culture conditions. Karyotyping of ADSCs was performed following one month culture by established protocols [37].…”
Section: Analysis Of Gene Expression and Karyotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the cells reached 50-60% confluence, they were washed twice with phosphate buffered saline (PBS), detached by 0.25% trypsin-EDTA (Gibco BRL) and then replated at a density of 3000 cells/cm 2 under the same culture conditions. Karyotyping of ADSCs was performed following one month culture by established protocols [37].…”
Section: Analysis Of Gene Expression and Karyotypingmentioning
confidence: 99%
“…We compared the growth of ADSCs in the medium containing 10% HAS and 10% FBS, and found that the growth is slower in the 10% HAS-supplemented medium ( Figure 3B). To improve the growth of ADSCs without the use of animal serum, we added two antioxidants (NAC and AsA2P) to the HAS-supplemented medium, where FGF-2, NAC and AsA2P supplements were collectively named MCA as previously described [37]. The morphology and growth of ADSCs between the following conditions were compared: 10% FBS, 10% HAS, 10% HAS+MCA and 2% HAS+MCA.…”
Section: Adscs Expansion In Different Culture Mediamentioning
confidence: 99%
“…With the development of molecular biology techniques, a number of diagnostic approaches have been utilized to diagnose fetal chromosome aneuploidy, such as FISH [ 9 , 10 ] short tandem repeat analysis (STR-QF-PCR) [ 11 ] and chromosomal microarray techniques. [ 12 ] All of these diagnostic techniques have the advantage of rapid diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Una célula diploide cuenta con dos copias de cromosomas, a diferencia de la monosomía, que es una alteración genética donde se cuenta con una única copia de estas, e incluso segmentos; dando lugar a enfermedades genéticas humanas 1 . Los cromosomas en anillo son una alteración estructural del material genético, en lugar de una pérdida o ganancia de éste, producto de una disfunción de los telómeros; y se atribuye a la muerte de células con aneuploidía secundaria, causada por inestabilidad durante la mitosis 2 ; es común encontrarlo en solo una porción de todas las células analizadas, como mosaicismo 3 , y suelen surgir de novo y no más del 1% son heredados 2 . Esta inestabilidad, nivel de mosaicismo y posición del punto de ruptura del cromosoma van a definir las características del paciente.…”
Section: Introductionunclassified